"The plural of silo is not ecosystem": qualitative study on the role of innovation ecosystems in supporting "Internet of Things" applications in health and care - Reidy, Claire; A’Court, Christine; Jenkins, Wilfred; Jani, Anant; Ramos, Andrew; Morys-Carter, Megan; Papoutsi, Chrysanthi (Digital health, 2023)
BackgroundInternet of Things (IoT) innovations such as wearables and sensors promise improved health outcomes and service efficiencies. Yet, most applications remain experimental with little routine use in health and care settings. We sought to examine the multiple interacting influences on IoT implementation, spread and scale-up, including the role of regional innovation ?ecosystems? and the impact of the COVID-19 context.MethodsQualitative study involving 20 participants with clinical, entrepreneurial and broader innovation experience in 18 in-depth interviews, focusing primarily on heart monitoring and assistive technology applications. Data analysis was informed by the NASSS (non-adoption, abandonment, scale-up, spread, sustainability) framework.ResultsInterviewees discussed multiple tensions and trade-offs, including lack of organisational capacity for routine IoT use, limited ability to receive and interpret data, complex procurement and governance processes, and risk of health disparities and inequalities without system support and funding. Although the pandemic highlighted opportunities for IoT use, it was unclear whether these would be sustained, with framings of innovation as ?disruption? coming at odds with immediate needs in healthcare settings. Even in an ?ecosystem? with strong presence of academic and research institutions, support was viewed as limited, with impressions of siloed working, conflicting agendas, fragmentation and lack of collaboration opportunities.ConclusionsIoT development, implementation and roll-out require support from multiple ecosystem actors to be able to articulate a value proposition beyond experimental or small-scale applications. In contexts where clinical, academic and commercial worlds collide, sustained effort is needed to align needs, priorities and motives, and to strengthen potential for good value IoT innovation.
Gesehen am 29.03.2023